Performance analysis of cooperative power-line communication system with signal space diversity - Sikri A.; Mathur A.; Srinivas K.V. (My University, 2025)
Power-line communication (PLC) is a cost-effective and promising communication technology for many smart grid applications. However, the presence of additive and multiplicative power line noises deteriorate the performance of a PLC system. In this paper, we propose signal space diversity (SSD) technique for a cooperative PLC system. The additive PLC channel noise is assumed to be Bernoulli-Gaussian–distributed. The multiplicative PLC channel noise gain is characterized by log-normal distribution. The closed-form expressions of the average symbol error rate (SER) and outage probability of cooperative PLC system with SSD have been derived in this paper. It has been shown that the proposed cooperative PLC system results in achieving better spectral efficiency, as well as the reliability of the received signal. © 2020 John Wiley & Sons, Ltd.